Historical Relationships with Social Physicology - Kissiya, Efilina (Jurnal Bimbingan dan Konseling Terapan, 2018)
Historical, in addition to having auxiliary science in his knowledge, history also establish relationships with other sciences, especially fellow social sciences. In this connection what happens is a relationship of mutual need, herein lies the difference with the concept of science Auxiliary history, where a more dominant history in need of help to uncover a problem, more precisely we can call it with a combination of two social sciences. The development of post-World War II History shows a strong tendency to use the social sciences approach in historical studies. One of the basic ideas is that: the descriptive-narrative history is no longer satisfactory to explain complex problems or symptoms in the event of History. Psychology is very related to mental and psychological human. Humans who become the object of historical study is not just explained about the actions taken and what is caused by the action? why someone does that action? These questions pertain to the psychological condition in question. Conditions that can be caused by stimuli from the outside or the environment, can also from within himself. The use of social phsychology in history, gave birth to the focus of the study of the history of mentality.